The jukebox musical : an interpretive history - Byrne, Kevin James; Fuchs, Emily (Routledge, Taylor & Francis Group, 2022)
"This is a comprehensive guide to the unique genre of the jukebox musical, delving into its history to explain why these musicals have quickly become beloved for multiple generations of theatregoers and practitioners. Providing a concise exploration of the three main categories of the jukebox musical - biographical, genre-specific and artist catalogue - this text is perfect for those wishing to learn more about this relatively recent and unique genre of theatre. It identifies the dramaturgical needs that arise in these productions and explains how certain works become critical darlings or fan favourites. Also offered are answers to a range of intriguing questions. How much information needs to be conveyed through song and how much can be left up to interpretation by the audience? What kinds of changes occur when a repertoire of songs is reimagined for the stage? In addition to these insightful explorations, it also reveals how creative teams tackle the unique challenge of weaving together plot and song in order to convey meaning, emotion, excitement and beauty in these increasingly popular forms of theatre. The Jukebox Musical: An Interpretive History is written for students, performers, and musical theatre enthusiasts alike: this is the ideal introduction to one of the Twenty First Century's most popular and successful stage genres"--